Measurement of the branching ratios for the decays of Ds(+) to eta pi(+), eta 'pi(+), eta rho(+), and eta 'rho(+) - Jessop, C; Lingel, K; Marsiske, H; Perl, M; Schaffner, S; Ugolini, D; Wang, R; Zhou, X; Coan, T; Fadeyev, V; Korolkov, I; Maravin, Y; et al. (1998)
Using a data sample with an integrated luminosity of 3.9 fb-1 collected in e+e annihilation with the CLEO-II detector at the Cornell Electron Storage Ring, we have measured the branching ratios for the decay modes D+s → (η,η′)π+ and D+s →(η,η′)ρ+ relative to D+s → φπ+. These decay modes are among the most common hadronic decays of the D+s, and can be related by factorization to the semileptonic decays D+s →(η,η′)ℓ+νl. The results obtained are compared with previous CLEO results and with the branching ratios measured for the related semileptonic decays. We also report results on the Cabibbo-suppressed decays of the D+ to the same final states.